1997
DOI: 10.1073/pnas.94.12.6087
|View full text |Cite
|
Sign up to set email alerts
|

Iron-sulfur cluster disassembly in the FNR protein of Escherichia coli by O 2 : [4Fe-4S] to [2Fe-2S] conversion with loss of biological activity

Abstract: The transcription factor FNR (fumarate nitrate reduction) requires the presence of an iron-sulfur (Fe-S) cluster for its function as a global transcription regulator in Escherichia coli when oxygen becomes scarce. The ability to adapt to changes in oxygen concentrations in the environment is common to many organisms. In the facultative anaerobe, Escherichia coli, the transcription factor FNR ( fumarate nitrate reduction) regulates a network of genes that facilitates adaptation to oxygen deprivation by providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
274
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(286 citation statements)
references
References 19 publications
11
274
1
Order By: Relevance
“…The mechanism whereby DNR can sense the signal molecule is not yet understood; it is certain, however, that DNR, which lacks conserved cysteines, is unable to form an Fe-S centre that can interact with the signal molecule as reported for the O 2 sensor FNR (Khoroshilova et al, 1995(Khoroshilova et al, , 1997 Green et al, 1996;Jordan et al, 1997 addition, the only evidence in the literature in which a member of the DNR class of regulators binds the target DNA in vitro was obtained by an electophoretic mobility shift assay using the P. aeruginosa DNR protein bound to haem (Giardina et al, 2008). The hypothesis of a haembased sensing is reasonable also in the light of a similar haem-based mechanism well known for the Rhodospirillum rubrum CooA protein (Shelver et al, 1997); in this case the CO molecule binds to the haem iron and triggers a conformational change, thus regulating the transcriptional activity (Lanzilotta et al, 2000).…”
Section: Dnr Activity Requires Haem Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism whereby DNR can sense the signal molecule is not yet understood; it is certain, however, that DNR, which lacks conserved cysteines, is unable to form an Fe-S centre that can interact with the signal molecule as reported for the O 2 sensor FNR (Khoroshilova et al, 1995(Khoroshilova et al, , 1997 Green et al, 1996;Jordan et al, 1997 addition, the only evidence in the literature in which a member of the DNR class of regulators binds the target DNA in vitro was obtained by an electophoretic mobility shift assay using the P. aeruginosa DNR protein bound to haem (Giardina et al, 2008). The hypothesis of a haembased sensing is reasonable also in the light of a similar haem-based mechanism well known for the Rhodospirillum rubrum CooA protein (Shelver et al, 1997); in this case the CO molecule binds to the haem iron and triggers a conformational change, thus regulating the transcriptional activity (Lanzilotta et al, 2000).…”
Section: Dnr Activity Requires Haem Biosynthesismentioning
confidence: 99%
“…The mechanism whereby DNR can sense the signal molecule is not yet understood; it is certain, however, that DNR, which lacks conserved cysteines, is unable to form an Fe-S centre that can interact with the signal molecule as reported for the O 2 sensor FNR (Khoroshilova et al, 1995(Khoroshilova et al, , 1997Green et al, 1996;Jordan et al, 1997). Moreover, spectroscopic evidence supports the hypothesis that haem is involved in NO sensing; in fact the DNR-haem complex is stable and can bind NO in the ferrous state to yield a pentacoordinate derivative (Giardina et al, 2008).…”
Section: Dnr Activity Requires Haem Biosynthesismentioning
confidence: 99%
“…The C-terminal DNA-binding domain recognizes specific FNRbinding sequences within FNR-controlled promoters (10). The N-terminal sensory domain contains five cysteine residues, four of which (12,(14)(15)(16)(18)(19)(20).The mechanism of the oxygen-mediated cluster conversion is of considerable current interest. Various mechanisms have been proposed for this process, including oxygen reduction to hydrogen peroxide through metal-centered oxidation (15) and oxygen reduction to water through sulfide-based oxidation (21).…”
mentioning
confidence: 99%
“…The C-terminal DNA-binding domain recognizes specific FNRbinding sequences within FNR-controlled promoters (10). The N-terminal sensory domain contains five cysteine residues, four of which (12,(14)(15)(16)(18)(19)(20).…”
mentioning
confidence: 99%
“…The sensory region of FNR has four conserved cysteine residues (Cys-20, -23, -29, and -122) that are essential for in vivo activity and capable of ligating an oxygen-sensitive [4Fe-4S] iron-sulfur cluster (6 -11). A variety of studies have revealed that the active form of FNR contains one [4Fe-4S] 2ϩ cluster/protein monomer that is converted to a [2Fe-2S] 2ϩ cluster, together with other, less well defined iron species, following exposure to oxygen both in vitro and in vivo (10,(12)(13)(14)(15). The switch from a cubane [4Fe-4S] cluster, bound to the protein by four cysteine thiol ligands that sit at the vertices of a tetrahedron, to a planar [2Fe-2S] cluster, also thought to possess four cysteine ligands but lying in a plane, suggests that cluster transformation on exposure to oxygen will provide a large conformational change in the N-terminal region of FNR, presumably thereby initiating the switch of the protein from a DNA binding state to one incapable of binding DNA (8).…”
mentioning
confidence: 99%